Transcription factors TP53 and SP1 and the osteogenic differentiation of dental stem cells - Oliver, Felthaus; Viale-Bouroncle, Sandra; Driemel, Oliver; Reichert, Torsten E.; Schmalz, Gottfried; Morsczeck, Christian (Differentiation (London), 2012)
Dental follicle is a loose connective tissue that surrounds the developing tooth. Dental follicle cells (DFCs) have a promising potential for tissue engineering applications including periodontal and bone regeneration. However, little is known about the molecular mechanisms underlying osteogenic differentiation. In a previous study we detected that more than 35% of genes that are regulated during osteogenic differentiation of DFCs have promoter binding sites for the transcription factors TP53 and SP1. However, the role of these transcription factors in dental stem cells is still unknown. We hypothesize that both factors influence the processes of cell proliferation and differentiation in dental stem cells. Therefore, we transiently transfected DFCs and dental pulp stem cells (SHED; Stem cells from human exfoliated decidiuous teeth) with expression vectors for these transcription factors. After overexpression of SP1 and TP53, SP1 influenced cell proliferation and TP53 osteogenic differentiation in both dental cell types. The effects on cell proliferation and differentiation were less pronounced after siRNA mediated silencing of TP53 and SP1. This indicates that the effects we observed after TP53 and SP1 overexpression are indirect and subject of complex regulation. Interestingly, upregulated biological processes in DFCs after TP53-overexpression resemble the downregulated biological processes in SHED after SP1-overexpression. Here, regulated processes are involved in cell motility, wound healing and programmed cell death. In conclusion, our study demonstrates that SP1 and TP53 influence cell proliferation and differentiation and similar biological processes in both SHED and DFCs. ► Dental stem cells (DSCs) can differentiate in vitro into mineralized cells. ► Molecular mechanisms of this process are not well understood. ► Genes regulated during osteogenesis possess promoter binding sites for TP53 and SP1. ► Gene functions were investigated after up- and down-regulation of P53 and SP1. ► TP53 modulates the differentiation whereas SP1 influences the proliferation of DSCs.